Performance measurement for supply chain management and evaluation criteria determination for reverse supply chain management - Kongar, E (SPIE-INT SOC OPTICAL ENGINEERING, 2004)
Today, since customers are able to obtain similar-quality products for similar prices, the lead time has become the only preference criterion for most of the consumers. Therefore, it is crucial that the lead time, i.e., the time spent from the raw material phase till the manufactured good reaches the customer, is minimized. This issue can be investigated under the title of Supply Chain Management (SCM). An efficiently managed supply chain can lead to reduced response time for customers. To achieve this, continuous observation of supply chain efficiency, i.e., a constant performance evaluation of the current SCM is required. Widely used conventional performance measurement methods lack the ability to evaluate a SCM since the supply chain is a dynamic system that requires a more thorough and flexible performance measurement technique. Balanced Scorecard (BS) is an efficient tool for measuring the performance of dynamic systems and has a proven capability of providing the decision makers with the appropriate feedback data. In addition to SCM, a relatively new management field, namely reverse supply chain management (RSCM), also necessitates an appropriate evaluation approach. RSCM differs from SCM in many aspects, i.e., the criteria used for evaluation, the high level of uncertainty involved etc., not allowing the usage of identical evaluation techniques used for SCM. This study proposes a generic Balanced Scorecard to measure the performance of supply chain management while defining the appropriate performance measures for SCM. A scorecard prototype, ESCAPE, is presented to demonstrate the evaluation process.
Keywords: supply chain management; reverse supply chain management; performance measurement; balanced scorecard; SYSTEMS; DESIGN; Engineering